Preparation of Transdermal Gel Containing l-Theanine for the Potential Treatment of Premenstrual Syndrome: A Preclinical Study - Kaana Ando; Ikumi Sugiyama; Yasuyuki Sadzuka (Mary Ann Liebert, 2024)
Background: Premenstrual syndrome (PMS) is experienced by many women who suffer from either its psychological or physical symptoms. Current treatment is limited to symptomatic therapy or oral contraceptives. On the other hand, l-theanine, which has a relaxant effect, has been reported to be useful for PMS, but its short half-life when administered orally makes it less effective. Permeability and properties of transdermal gel containing l-theanine were evaluated as a preclinical study of PMS symptoms relief formulation. Materials and Methods: Lyogel composed of stearic acid, stearyl alcohol, and propylene glycol was selected. The ratio of these components and the preparation method were investigated. Permeation of Strat-M membranes was evaluated by using Franz cells (in vitro). Moreover, lyogel was applied to institute of cancer research mice's backs for 10 days to examine the permeability of l-theanine. Results: l-Theanine solution did not permeate the Strat-M membrane at all in the permeation study, but lyogel allowed l-theanine to permeate. When the composition of lyogel was 4.4:11.1:296 (mmol) for stearic acid, stearyl alcohol, and propylene glycol, l-theanine absorption through Strat-M membrane was better. In skin permeation study using mice, l-theanine was detected in the serum, that is, it was proven that l-theanine penetrated the skin. Conclusion: The preparation of transdermal gels contained l-theanine was investigated as a preclinical study. The skin permeability of semisolid formulations of hydrophobic ointments, hydrophilic ointments, oily creams, creams, and lyogel containing theanine was compared and found that lyogel was the best. The composition of lyogel was also studied to obtain a formulation with good application comfort. Although it is suggested that this lyogel could be tested in clinical studies to determine whether it is effective for relief of PMS symptoms, lyogel may be suitable as an easy-to-use l-theanine-containing formulation for women that can relieve PMS symptoms.